The Integral Role of Multidisciplinary Teams in the Management of Chronic Illnesses: Enhancing Patient Outcomes through Collaborative Care Models - Alnahidh, Alhanouf Abdullah Abdulrahman; Alanazi, Salihah Matar Ibrahim; Alghamdi, Ahmed Saleh Ahmed; Alblawi , Suliman; Al-Koikibi, Amirah Sayah Sabih; Shikhani, Fadih Mohammed Hassan; Al Amri , Safiah Saad Mohammad; Jabour , Hashima Makki Mohammed; Alsubaie, Muflih Saad; Alwabari, Israa Mohammed Hussain; Bouaitte, Basim Ibrahim Mohammed; Alshmmari, Mantahaa Yousef; et al. (Journal of Ecohumanism, 2024)
Background: Chronic illnesses are a leading cause of morbidity and mortality worldwide, necessitating complex management strategies that often exceed the capacities of individual healthcare providers. Multidisciplinary teams (MDTs) are increasingly recognized as essential for delivering comprehensive patient care in chronic disease management. Methods: This review synthesizes findings from various studies published between 2000 and 2023, utilizing databases such as PubMed, Google Scholar, and Scopus. Key search terms included “multidisciplinary teams,” “chronic disease management,” and “pharmacists’ roles.” The focus was on the impact of pharmacists within MDTs and their contributions to patient outcomes. Results: The integration of pharmacists into MDTs enhances chronic illness management by improving medication adherence, reducing medication errors, and fostering effective communication among team members. Case studies illustrate how collaborative efforts among physicians, pharmacists, nurses, and other healthcare professionals lead to improved patient satisfaction, lower healthcare costs, and better clinical outcomes. Conclusion: Effective collaboration within MDTs is vital for optimizing chronic disease management. Engaging pharmacists not only improves medication management but also strengthens the overall care process. Future research should explore standardized models for integrating pharmacists into MDTs and assess their long-term impact on patient health outcomes.